SISTEM INFORMASI DESA BERBASIS WEB (STUDI KASUS DESA WEDING) - Zaenal Mustofa; Mokhamad Iklil Mustofa (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2018)
Abstract The rapid development of technology, especially the internet which is followed by the movement/mobilization of the community in fulfilling the needs of life and education, as well as public awareness of the needs of village administrative requirements, such as family cards, identity cards, birth certificates, land ownership certificates , data collection of the final voters list and other village administrations, so that the village apparatus must be extra in carrying out data collection on the village in an integrated manner, so that it can be accessed anywhere via an internet connection without returning to their hometown. The village apparatus can classify the conditions of the community with certain categories using this system, such as education and welfare. Villagers who migrate outside the island want to make birth certificates, renew e-ID cards, family cards, etc., do not need to go back to their hometowns, just send physical files and scan files that are expected to the "Village Web Information System" application to request the documents. Furthermore, if there is a presidential election, then the parties registered with DPT can ask information through the info menu facility available in this system, so that election file files can be sent to the address of villagers who migrate outside the island / city to be able to use their voting rights. All village data will be recorded / records related to the current domicile, such as education, employment, birth certificate, e-ID card, ownership of land certificates, payment of land and building taxes, and other village administration completeness